2008
DOI: 10.1002/jbm.a.32216
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of alginate/gelatin blend films for cardiac tissue engineering

Abstract: The aim of this work was the preparation of blends based on alginate and gelatin, with different weight ratio, to combine the advantages of these two natural polymers for application in cardiac tissue engineering. The physicochemical characterization, performed by Fourier transform infrared spectroscopy, differential scanning calorimetry and thermogravimetric analysis, revealed a good miscibility and the presence of interactions among the functional groups of pure biopolymers. Concerning the swelling and degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
131
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(141 citation statements)
references
References 19 publications
2
131
1
Order By: Relevance
“…Rosellini et al [23] showed that in vitro degradation behavior at 37 ºC of gelatin crosslinked with GA films in PBS is quite similar to that obtained in PBS collagenase solution. Electrospun cross-linked samples were immersed in PBS solution and the extent of hydrolytic degradation was determined (Figure 2).…”
Section: Hydrolytic Degradationmentioning
confidence: 72%
See 1 more Smart Citation
“…Rosellini et al [23] showed that in vitro degradation behavior at 37 ºC of gelatin crosslinked with GA films in PBS is quite similar to that obtained in PBS collagenase solution. Electrospun cross-linked samples were immersed in PBS solution and the extent of hydrolytic degradation was determined (Figure 2).…”
Section: Hydrolytic Degradationmentioning
confidence: 72%
“…Rosellini et al [23] studied the effect of the presence of collagenase in the phosphate buffer saline (PBS) solution during in vitro degradation of gelatin scaffolds cross-linked with GA, and found that a mainly hydrolytic degradation process occurs due to solvation and depolymerization of the polymeric chains [24].…”
mentioning
confidence: 99%
“…The highly hydrated network structure permits the exchange of gases and nutrients and makes them an attractive option for the 55 formation of "inks" for bioprinting. Blending of hydrogels provides an opportunity by which properties specific to each respective hydrogel component can be combined to tailor the overall hydrogel towards facilitating specific requirements 8,9 . Alginates (Alg) are naturally occurring polysaccharides 60 isolated from brown algae with linear blocks of (1, 4)-linked β-Dmannuronate (M) acid and α-L-guluronic acid (G) residues 10,11 .…”
mentioning
confidence: 99%
“…Alginate-gelatin (Alg-Gel) blends have been reported as potential drug delivery carriers 8,9 , enzyme immobilisation beads 5 22 , wound dressing fibres 23 , and sponges for tissue matrices 24 . Among the studies related to bioprinting, Yan and co-workers [25][26][27] have attempted to print 3D scaffolds from alginate-gelatin blends.…”
mentioning
confidence: 99%
“…HA is gaining popularity as a biomaterial for tissue engineering and tissue regeneration due to its high biocompatibility and low immunogenicity (Zheng et al, 2004;Leach et al, 2015) as well as its ability to promote cell migration (Yoo et al, 2005). Previously, it has been shown that rate of cell proliferation and cardiomyogenic differentiation of C2C12 myoblasts was significantly increased with a film like scaffold, which was produced by mixing alginate and gelatin (Rosellini et al, 2009), and films including gelatin in high proportions were proposed as ideal scaffolds. Considering the previous findings and gelatin's effect in induction of cardiomyogenic differentiation, as well as its positive effects on cell attachment and expansion, gelatin concentration in the HA/G plasma gels was kept higher than the HA concentration in the present study.…”
Section: Discussionmentioning
confidence: 99%